Why policy reforms fail to improve logging practices: the role of governance and norms in Peru - Smith, J.; Colan, V.; Sabogal, C.; Snook, Laura K. (2006)
Although policies to improve forest management have been widely introduced, poor logging practices remain prevalent in tropical forests. We assess whether recent radical changes in forestry laws in Peru will result in significant improvements in logging practices. We adapt North's conceptual framework of institutional change to analyze the impact of governance on loggers' norms and argue that improvements in logging practices will require changes in both laws and norms. The analysis uses survey and field evaluation data on logging practices in Peru, as well as secondary sources. Results show that bringing about radical changes in logging practices is particularly difficult in countries with a history of governance failures in the timber sector. In Peru, governance failures that have promoted norms inconsistent with good management are government's perceived lack of interest in long-term timber management, inconsistent forestry laws, perceived discrimination against the timber sector, and ineffective law enforcement. As a result of decades of these governance failures, loggers developed a short-term perspective on timber extraction and felt entitled to violate government's laws. Poor logging practices continued under the new law because of governance failures. The Peruvian experience shows that changing laws radically is often easier than avoiding governance failures in implementation. While some governance failures were partially rectified, others assumed added significance under the provisions of the new law. Decentralization also exacerbated existing and new governance problems. These failures reinforced existing norms and may, in addition, lead to norms condoning corruption. Modifications need to occur both in norms and in logging laws to reduce the inconsistency between the two. Notable improvements in governance will be required to bring about changes in norms. Changes in the logging system are therefore likely to be far less revolutionary, and to take far longer, than envisioned.